MODIFICATION OF MIXED STRUCTURE TiO2 NANOPOROUS-NANOTUBE ARRAYS WITH CdS NANO PARTICLE AND THEIR PHOTO ELECTRO CHEMICALPROPERTIES - Hedi Surahman; Supriyono Supriyono; Yuni K Krisnandi; Jarnuzi Gunlazuardi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
MODIFICATION OF MIXED STRUCTURE TiO2 NANOPOROUS-NANOTUBE ARRAYS WITH CdS NANO PARTICLE AND THEIR PHOTO ELECTRO CHEMICALPROPERTIES. In thiswork, a mixed structure TiO2 with a top nanoporous layer and an underneath highly ordered nanotube arrays layer (TNPs-NTAs) were prepared by anodic oxidation of Ti foil under controlled anodization time in an electrolyte containing fluoride ion,water and ethylene glycol. CdS nanoparticles (NPs) was deposited onto the mixed structure of TiO2 by Successive Ionic Layer Adsorption and Reaction (SILAR) with an aim toward tuning the photoelectrochemical performance to visible region. Themorphology, elemental composition, crystal structure, optical properties and photoelectrochemical performance of TNPs-NTs and CdS modified (CdS/TNP-NTAs) samples were characterized by Field Emisi Scanning Electron Microscope (FESEM), Electron Dispersive Spectroscopy (EDS), X-Ray Diffractometer (XRD), Diffuse Reflactance Spectroscopy (DRS) and electrochemical working station respectively. The results indicate that CdS nanoparticles uniformly decorated on top of surface and inner wall of TNPs-NTs sample. No clogging of CdS-NP at the mouth TNPs-NTAs was observed. The CdS/TNP-NTs show an increasing in the visible light adsorption and photocurrent response. Under white light illumination (9.93 mW/cm2), we found that the CdS/TNPs-NTAs have an optimum photocurrent density of 1.16 mA/cm2 , corresponding to energy photoconversion efficiency of 9.75%, which is 7 times higher than that of the bare TiO2 (TNPs-NTAs). The increase of photocurrent is attributed to the enhancement of charge separation efficiency and improved electron transport.